Characterization of erythrose reductases from filamentous fungi - Jovanović, Birgit (Springer, 2013)
Proteins with putative erythrose reductase activity have been identified in the filamentous fungi Trichoderma reesei, Aspergillus niger, and Fusarium graminearum by in silico analysis. The proteins found in T. reesei and A. niger had earlier been characterized as glycerol dehydrogenase and aldehyde reductase, respectively. Corresponding genes from all three fungi were cloned, heterologously expressed in Escherichia coli, and purified. Subsequently, they were used to establish optimal enzyme assay conditions. All three enzymes strictly require NADPH as cofactor, whereas with NADH no activity could be observed. The enzymatic characterization of the three enzymes using ten substrates revealed high substrate specificity and activity with D-erythrose and D-threose. The enzymes from T. reesei and A. niger herein showed comparable activities, whereas the one from F. graminearum reached only about a tenth of it for all tested substrates. In order to proof in vivo the proposed enzyme function, we overexpressed the erythrose reductase-encoding gene in T. reesei. An increased production of erythritol by the recombinant strain compared to the parental strain could be detected.